2020
DOI: 10.3390/ijerph17249186
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Survey Non-Response in a Cross-Sectional Survey of Persons with an Axial Spondyloarthritis or Osteoarthritis Claims Diagnosis

Abstract: Non-response in surveys can lead to bias, which is often difficult to investigate. The aim of this analysis was to compare factors available from claims data associated with survey non-response and to compare them among two samples. A stratified sample of 4471 persons with a diagnosis of axial spondyloarthritis (axSpA) and a sample of 8995 persons with an osteoarthritis (OA) diagnosis from a German statutory health insurance were randomly selected and sent a postal survey. The association of age, sex, medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therefore, their claims data offers an unselected view on the uptake of services of a broad collective of that population. German SHI claims data have also been used for investigations in nephrology [27][28][29] and when dealing with patients with other chronic conditions [30,31]. We analyzed anonymous claims data of two of the largest SHIs in Germany: DAK-Gesundheit (Deutsche Angestellten Krankenkasse) and SBK (Siemens Betriebskrankenkasse).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, their claims data offers an unselected view on the uptake of services of a broad collective of that population. German SHI claims data have also been used for investigations in nephrology [27][28][29] and when dealing with patients with other chronic conditions [30,31]. We analyzed anonymous claims data of two of the largest SHIs in Germany: DAK-Gesundheit (Deutsche Angestellten Krankenkasse) and SBK (Siemens Betriebskrankenkasse).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, relatively more women were included in the group with the TNFi serum trough level measurement, than in the group that did not have this measurement. A possible explanation could be that women have a higher likelihood of responding to research invitations [ 34 ]. Furthermore, patients without the serum trough level measurement had a longer treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation from PROCLAIR on persons with an osteoarthritis or an axSpA‐diagnosis had already revealed that survey responsiveness differed according to age and sex. Moreover, survey responders visited specialists and received health care interventions, such as vaccinations or prescriptions for specific drugs and physical therapy, more frequently than non‐responders 25 . While those differences between survey responders and non‐responders probably affect the PPVs, there is no reason to believe that they would change the ranking of the most suitable algorithm to identify RA patients in German claims data.…”
Section: Discussionmentioning
confidence: 99%